Aggressive Trimodality Therapy for T1N2M1 Nonsmall Cell Lung Cancer with Synchronous Solitary Brain Metastasis: Case Report and Rationale - Timothy N. Showalter; Alexander Lin (Case Reports in Medicine)
Aggressive treatment, including resection of both metastasis and primary tumor, has been studied for non-small cell lung cancer patients with synchronous solitary brain metastasis. Involvement of mediastinal lymph nodes is considered a poor prognostic factor and a contraindication to surgical resection of the primary lung tumor after treatment for brain metastasis. Here we present the case of a patient who presented with a Stage IV T1N2M1 non-small cell lung cancer with synchronous solitary brain metastasis. He is alive and without evidence of disease two years after aggressive, multimodality treatment that included craniotomy, whole-brain radiation therapy, thoracic surgery, chemotherapy, and mediastinal radiation therapy.